PELAYANAN PEMERIKSAAN MATA DAN PENYULUHAN RETINOPATI DIABETIK - Surasmiati, N.M.A.; Suryaningrum, I.G.A.R.; Wijayati, M.P.; Suryathi, N.M.A.; Suryanadi, N.M. (Buletin Udayana Mengabdi; Vol 23 No 4 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i04.p02, 2023)
Background: Based on the Rapid Assessment and Avoidable Blindness survey, it was found that the blindness rate in Indonesia was 3 percent, while in Bali it was 2 percent. This prevalence data can provide important information to conduct an activity to overcome the problem of eye health disorders. Research Objective: Community in banjar Biaung, Kesiman, Denpasar Timur. Methods: This program included eye examination and diabetic retinopathy counseling. The eye examination includes visual acuity, eye pressure, anterior segment, and posterior segment of the eye. Examination of the posterior segment using a direct funduscopy and fundus radiographs, and assessed for retinopathy. Counseling given about diabetic retinopathy is a diabeticeye complication so knowing the early symptoms will help prevent blindness due to diabetes. Results: This social program involved 16 doctors from the Udayana University Eye Health Study Program. A total of 124 residents participated with the majority being over 40 years old and most of them with normal visual acuity. As much as 2.2% including blind criteria according to WHO. Retinopathy was obtained as much as 5.6% and almost all of them were in the mild-moderate non-proliferative phase. This program also distributed lubricant eye drops, masks, and reading glasses. Conclusion: The rate of blindness discovered in Banjar Biaung is comparable to the prevalence of blindness in Bali. Keywords: visual acuity, intraocular pressure, anterior segment, posterior segment, diabetic retinopathy